Implementasi Named Entity Recognition Pada Factoid Question Answering System Untuk Cerita Rakyat Indonesia - Yulia Kurniawati; Indriati Indriati; Putra Pandu Adikara (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Regional legend or folklore is a story that developed among the various cultures of Indonesia that have been down and down inherited. Folklore is a story of the past that is believed to be the true event, usually the folktale is the origin of a place. The lack of an attractive means of introducing folklore is one of the reasons for the lack of interest of Indonesian folklore. In addition, the level of understanding of children who are still less than adults cause them to easily forget the story of the people when they are less understood to the story of the people of Indonesia. This study aims to facilitate the children in understanding the story. Therefore, the researcher makes question answering system by using Named Entity Recognition method. The classification of named entity in this research using naive bayes method. In this research used four named entity to recognize the next word will be candidate for answers such as product, person, location and none. Where none is an entity. In addition, the type of question that can be asked on the question answering system is Factoid Question is a question that the answer is a short and solid fact not a description. The data used are five folk stories of Indonesia obtained from the internet and the classification of Named Entity has a precision value of 34.22%, the accuracy of NE classification of 64.65% and recall 13.13% while for question answering accuracy system obtained accuracy of 16.7%.